Cape Gooseberry Husk for the Removal of CECs from Wastewater: A Biosorption Study - Abdel Salam, Jehan (AUC Knowledge Fountain, 2021)
Food and beverage industries produce large amounts of fruit wastes that are normally discarded every year. Meanwhile, these industries along with the pharmaceutical industries discharge wastewater effluents that are loaded with contaminants of emerging concern (CECs). Recent research is directed towards finding alternative cost effective and sustainable solutions for treating wastewater. In this regard, we investigated cape gooseberry husk as a potential biosorbent for the removal of caffeine (CA) and salicylic acid (SA), as examples of CECs, from wastewater. Three different types of husk were investigated; un-activated husk (H), and chemically activated husks (H350 and H500) prepared by acid treatment and heating at 350oC and 500oC, respectively. The husks were characterized using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), CHNS analysis, Brunauer- Emmet- Teller (BET), zeta potential (ZP) and point of zero charge (PZC) measurements. All three types of husks were primarily mesoporous and negatively charged. The activation of the husk resulted in an increase in the surface area, pore volume and average pore size. The activation also led to the disappearance of some functional groups due to husk carbonization, as confirmed by FTIR. The single-component adsorption of SA and CA onto the three husks was investigated at different pHs and pH 6.5 was selected as the optimal pH for operation. The effect of initial concentration was also examined at the optimal pH. At the low range of concentrations of up to 70 mg/L, the maximum removal efficiencies reached up to 59%, 85%, and 85% for H, H350 and H500, respectively. At the higher concentration range (70-280 mg/L), the percent removal averaged around 55% for the three husks. Similarly for CA, up to 56%, 65% and 63% respective removal efficiencies were obtained for H, H350, and H500, below 85 mg/L. They, as well, averaged around 55% similar to SA adsorption, in most of the employed range of concentrations (82-400 mg/L). Adsorption was influenced by the textural properties along with the surface charge on the adsorbent. The adsorption of SA and CA onto all different types of husk was best described by the pseudo-second-order kinetic model. H350 exhibited high rates of adsorption towards SA and CA, since adsorption was likely governed by fast surface reaction kinetics. The adsorption isotherms for CA onto H, H350 and H500 were best fitted to the Linear adsorption model, and same applied for SA adsorption onto H. For the adsorption of SA onto H350 and H500, the Freundlich isotherm model was a better fit. The isotherm parameters along with energies of adsorption suggested physisorption with higher favorability for the activated husks, as well as stronger binding of CA onto the husk as compared to SA binding. It was proposed that CA interacts electrostatically with the husk, while SA binds through weak physical interactions like van der Waals’ and H-bonding. H350 was chosen as the optimal husk for further binary studies since it offered rapid adsorption with efficient removal towards SA and CA. In binary systems, CA adsorption was highly favored over SA adsorption, possibly owing to its electrostatic interactions. Additionally, the husk was successfully regenerated and re-used for up to 4 consecutive cycles.